What are the determinants of hiring? The role of demand and supply factors - Stefan Eriksson; Karolina Stadin (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2015)
In this paper, we study the relative importance of demand and supply factors for hiring. We use a search-matching model with imperfect competition in the product market to derive an equation for total hiring in a local labor market and estimate it on Swedish panel data. If product markets are imperfectly competitive, product demand shocks should have a direct effect on employment. Our main finding is that product demand is important for hiring. This highlights the importance of taking imperfect competition in the product market into account in studies of employment dynamics and hiring. We also find that the number of unemployed workers has a positive effect on hiring, confirming the importance of search frictions. Hence, both demand and supply factors seem to matter for hiring.
Keywords: E24; J23; J64; 330; hiring; search-matching; imperfect competition; unemployment